Bone marrow-derived mesenchymal stem cells promote cell proliferation of multiple myeloma through inhibiting T cell immune responses via PD-1/PD-L1 pathway. Issue 7 (3rd April 2018) - Chen, Dandan; Tang, Ping; Liu, Linxiang; Wang, Fang; Xing, Haizhou; Sun, Ling; Jiang, Zhongxing
ABSTRACT: Objectives: This study aims to explore the effect of bone marrow mesenchymal stem cells (BMSCs) on multiple myeloma (MM) development and the underlying mechanism. Materials and Methods: BMSCs from C57BL/6 J mice were isolated and the third passage was used for subsequent experiments. Additionally, a series of in vitro transwell coculture assays were performed to explore the effects of BMSCs on the proliferation of MM cells 5TGM1 and CD4 + T cells. Furthermore, a 5TGM1-induced MM mice model was established. Moreover, PD-L1 shRNA was transfected into BMSCs to investigate whether PD-1/PD-L1 pathway involved in BMSCs-mediated regulation of T cells and MM growth. Results: Data revealed that BMSCs significantly promoted 5TGM1 proliferation in a dose-dependent manner. Furthermore, BMSCs administration exerted stimulatory effects on MM development in terms of shortening the mouse survival rate, promoting tumor growth, and enhancing inflammatory infiltration in the MM model mice. Moreover, BMSCs decreased the percentage of Th1 and Th17 cells, whereas increased that of Th2 and Treg cells. Their corresponding cytokines of these T cell subsets showed similar alteration in the presence of BMSCs. Additionally, BMSCs significantly suppressed CD4 + T cell proliferation. We also found that PD-L1 shRNA inhibited 5TGM1 proliferation likely through activation of CD4 + T cells. Further in vivo experiments confirmed that PD-L1 inhibition attenuated BMSCs-induced MM growth, inflammation infiltration and imbalance of Th1/Th2 and Th17/Treg. Conclusion: In summary, our findings demonstrated that BMSCs promoted cell proliferation of MM through inhibiting T cell immune responses via PD-1/PD-L1 pathway.